Intermediate Microeconomics - Emerson, Patrick M. (Open textbook library., 2019)
Intermediate Microeconomics is a comprehensive microeconomic theory text that uses real world policy questions to motivate and illustrate the material in each chapter. Intermediate Microeconomics is an approachable yet rigorous textbook that covers the entire scope of traditional microeconomic theory and includes two mathematical approaches, allowing instructors to teach the material with or without calculus. With real-world policy topics as an entree into each subject, Intermediate Microeconomics will help students engage with the material and facilitate learning not only the concepts, but their importance and application as well.